Economies of Scale and Efficiency Measurement in Switzerland's Nursing Homes - Mehdi Farsi; Massimo Filippini; Diego Lunati (Swiss Journal of Economics and Statistics, 2008)
This paper examines the cost efficiency in the nursing home industry, an issue of concern to Swiss policy makers because of the explosive growth of national expenditure on elderly care and the aging of the population. A stochastic cost frontier model has been applied to a panel of 1780 observations from 356 nursing homes operating over 1998-2002 in Switzerland. We compare the estimation results from different econometric techniques focusing on the specification of unobserved heterogeneity across firms. The potential effects of such unobserved factors on the estimation results and their interpretation have been discussed. The findings suggest that the economies of scale are an important potential source of cost reduction in a majority of Swiss nursing homes. Moreover the average performance of a representative nursing home is very close to the estimated best practice.
Keywords: C13; C21; D24; H70; I11; I18; L30; 330; cost efficiency; economies of scale; nursing homes; stochastic frontier; panel data